Immunological Reconstitution in Children After Completing Conventional Chemotherapy of Acute Lymphoblastic Leukemia is Marked by Impaired B-cell Compartment - Koskenvuo M; Ekman I; Saha E; Salokannel E; Matomaki J; Ilonen J; Kainulainen L; Arola M; Lahteenmaki PM (WILEY-BLACKWELL, 2022)
Humoral and cellular immunity were studied in 28 children completing conventional treatment of standard-risk (SR) or intermediate-risk (IR) acute lymphoblastic leukemia (ALL). Both naive and memory B cells were most severely affected and showed slow recovery during the 2-year follow-up, while the T-cell compartment showed only minor changes. Immunoglobulins and IgG subclasses, components, and antibodies against vaccine-preventable diseases were not significantly affected. In conclusion, immune recovery after conventional chemotherapy for SR and IR ALL is marked by B-cell depletion, but otherwise did not show any severe deficiencies in lymphocyte function. (C) 2016 Wiley Periodicals, Inc.